A EPIDEMIOLOGIA DA TUBERCULOSE NO SISTEMA PENITENCIÁRIO NO MUNICÍPIO DE PORTO VELHO ENTRE OS ANOS DE 2019-2023. - Marcellino, Pollyane Tayse Costa Leitão (2024)
This article aims to analyze the epidemiological data of Tuberculosis in the penitentiary system in the municipality of Porto Velho between the years 2019-2013. The present study has a descriptive epidemiological character and was carried out using secondary data from the Disease and Notification Information System (SINAN NET), with data collected in October 2023, based on information made available by the State Health Surveillance Agency of Rondônia , analyzing the period between 2019 and 2023. It is concluded that among the prison population in the municipality of Porto Velho, the preponderance is males, aged between 20 and 34 years, with high cure rates, low treatment abandonment and some cases of co-infection with the HIV virus, with the predominance of the pulmonary form.